The finite element methods on oral rehabilitation: New trend for endodontically treated teeth - Juliana Santos Oliveira; Érica Alves Gomes; Carolina de Andrade Lima Chaves; Yara T. Côrrea Silva Sousa (Brazilian Dental Science)
The aim of this study is to present the applicability of Finite element analysis (FEA) in oral rehabilitation, especially in endodontically treated teeth, based on its indication, methods, advantages and limitations through a literature review. The search was conducted on National Library of Medicine’s Pub Med, Google search and Science Direct databases including the keywords “finite element analysis”, “oral rehabilitation” and “endodontics”. A total of 412 articles were found, 42 were carefully selected by two subject matter experts for discussion including 21 articles focusing on the applicability of FEA to endodontically treated teeth. The FEA is a versatile, low-cost and efficient approach for reliable evaluation of complex structures, as oral rehabilitation treatments.